1986
DOI: 10.4319/lo.1986.31.1.0125
|View full text |Cite
|
Sign up to set email alerts
|

The dominant processes of sediment distribution and focusing in a small, eutrophic, monomictic lake

Abstract: There is evidence for 10 mechanisms of sediment distribution in small lakes. The sediment accumulation rates measured from a common horizon in cores from 64 sites on Esthwaite Water, U.K., were used to determine the relative importance of these mechanisms on the distribution of sediment in the lake.River inflows generally produced localized effects but there were indications of periodic turbidity flows to the deepest point of the lake from the major inflow. Active sediment focusing processes were the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 28 publications
5
105
0
1
Order By: Relevance
“…During permanent deposition from the source to the bottom of the lake, sedimentary organic matter is influenced by a variety of factors including river inputs, underwater topography, and lake wind and induced waves, which eventually leads to different spatial distribution patterns [19][20][21][22][23][45][46][47]. In some small lakes, the spatial distribution of sedimentary organic matter is relatively simple, owing to one factor showing the greatest effect [48].…”
Section: Influence Factors and Paleolimnological Significancementioning
confidence: 99%
“…During permanent deposition from the source to the bottom of the lake, sedimentary organic matter is influenced by a variety of factors including river inputs, underwater topography, and lake wind and induced waves, which eventually leads to different spatial distribution patterns [19][20][21][22][23][45][46][47]. In some small lakes, the spatial distribution of sedimentary organic matter is relatively simple, owing to one factor showing the greatest effect [48].…”
Section: Influence Factors and Paleolimnological Significancementioning
confidence: 99%
“…Not all of the four sediment focusing mechanisms identified by Hilton et al (1986a) are relevant to Llyn Conwy. Given that this lake is oligotrophic, hosts virtually no aquatic macrophytes and has extremely low turbidity and nutrient loadings, the organic degradation mechanism can be readily discounted here.…”
Section: Evaluation Of Alternative Sediment Focusing Mechanismsmentioning
confidence: 99%
“…An early application of seismic stratigraphic survey by Cronin et al (1993) to another small upland lake in Wales found limited evidence for slumping of highly organic sediments on slopes of about 15 degrees (26%) and it would be interesting to undertake bed imaging (e.g., using sidescan sonar) in Llyn Conwy to investigate the prevalence of slides and slumps. Hilton et al (1986a) also describe a process that they term "intermittent complete mixing," driven by widespread resuspension, mixing, and settling. This leads to sediment focusing by virtue of the greater water column sediment mass in deeper water.…”
Section: Evaluation Of Alternative Sediment Focusing Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations